Strategi Penyiaran Program Sawo Matang Di Radio Gajah Mungkur FM Untuk Mempertahankan Pendengar - Putri, Warastri Amalia; Sarjono, Herning Suryo; Kusumo Aji, Haryo (Solidaritas, 2024)
In defense Listeners to radio broadcast programs need appropriate broadcasting strategies. In Wonogiri, Central Java, there are private radio stations that have air quite a long time ago, namely Radio Gajah Mungkur Fm. Radio Gajah Mungkur Fm has various program events, one of which is Sapa Wonogiri Approaching Evening or Sapodilla . Brown use strategies to can maintain the listener. With using a broadcast strategy in manage an event program with ok, got it maintain listener. Study This use theory strategy broadcasting programs according to Susan Tyler Eastman. Research methods used researcher in study This is qualitative descriptive. Data collection techniques were carried out through observation, interview as well as documentation. Research result This show that the strategy for broadcasting the Sawo Matang program includes five things, namely conformity strategy Where covers three matter important that is scheduling, selection program type and principal problem to need listener. Formation strategy done with form habit Listen to the results from exists scheduling of Sawo Matang broadcast programs which is not Once change and exist effort promotion through making adverts and ad spots. Control strategy current listener done with set standard quality with guard quality of the Sawo Matang program so that can maintain listener. Storage strategy program resources are carried out with save it through device computer for later Can used return. Power strategy towing mass of the Sawo Matang program done with package an interesting program maybe, okay through style language and also use social media For broadcast programs. Deep conclusion study this, strategy broadcasting the is a strategy for maintain listener as well as expand Sawo Matang listeners. Keywords : Broadcasting strategy , Sawo Matang , defend listeners